Incubator Temperature and Oxygen Concentration at the Plateau Stage Affects Intestinal Maturation of Turkey Embryos - Christensen, V .L.; Wineland, M.J.; Yildirum, I.; Ort, D.T.; Mann, K.M. (International Journal of Poultry Science, 2004)
The plateau stage in oxygen consumption of turkey embryos occurs at 25 and 26 days of incubation when many embryos die. The plateau stage creates hypoxia, hypercapnia and presents a paradox for growth and embryo metabolism. Prior to the plateau, vital tissues accumulate glycogen to ensure embryonic survival through anaerobic metabolism during the plateau. Intestinal maturation at the plateau demands great amounts of energy. Therefore, the objective of the study was to define the temperature and oxygen concentrations at the plateau that affect intestinal maturation. Three experiments were conducted to test incubator conditions during the plateau stage and their affect on intestinal maturation. In Experiment 1, turkey embryos at the plateau stage were exposed to 36, 37, 38 or 39°C. In Experiment 2, embryos at the plateau stage were exposed to 17, 19, 21 or 23% oxygen concentrations, and in Experiment 3, the extreme levels of temperature and oxygen treatments were combined to test interaction effects on intestinal maturation. Elevating temperature depressed intestinal weight but not length. The elevated temperature also depressed intestinal maltase and alkaline phosphatase activities indicating inhibited function. Increasing oxygen had little effect on intestinal weight or length, but hypoxia increased maltase and decreased alkaline phosphatase activities in hatchlings. When examined in a factorial arrangement, temperature and oxygen displayed independent effects on growth and function and did not interact. Thus, incubator temperature greater than 37°C and oxygen concentrations less than 19% during the plateau stage delay intestinal maturation.